2013
DOI: 10.1002/hipo.22162
|View full text |Cite
|
Sign up to set email alerts
|

Pattern separation and pattern completion in Alzheimer's disease: Evidence of rapid forgetting in amnestic mild cognitive impairment

Abstract: Over the past four decades, the characterization of memory loss associated with Alzheimer's disease (AD) has been extensively debated. Recent iterations have focused on disordered encoding versus rapid forgetting. To address this issue, we used a behavioral pattern separation task to assess the ability of the hippocampus to create and maintain distinct and orthogonalized visual memory representations in patients with amnestic mild cognitive impairment (aMCI) and mild AD. We specifically used a lag-based contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(135 citation statements)
references
References 79 publications
(124 reference statements)
5
129
0
1
Order By: Relevance
“…The comparisons of older adults, individuals with aMCI and with AD in the study of Ally et al (2013), which formed the basis for the present investigation, appeared to uncover a form of rapid interference-based forgetting. Individuals with aMCI and AD showed decreased pattern separation scores (BPS) with increasing 'lag'.…”
Section: Implications For Behavioural Measures Of Pattern Separationmentioning
confidence: 76%
See 3 more Smart Citations
“…The comparisons of older adults, individuals with aMCI and with AD in the study of Ally et al (2013), which formed the basis for the present investigation, appeared to uncover a form of rapid interference-based forgetting. Individuals with aMCI and AD showed decreased pattern separation scores (BPS) with increasing 'lag'.…”
Section: Implications For Behavioural Measures Of Pattern Separationmentioning
confidence: 76%
“…Although very interesting, the differing patterns of performance in pattern separation on the behavioural task demonstrated by Ally et al (2013) across normal ageing, aMCI and AD individuals must remain very tentative since their manipulation confounded two critical dimensions identified within theories of forgetting (Altmann & Gray, 2002): namely the temporal interval elapsing (that is, between encoding of an 'old' item into memory and its reintroduction later as a 'similar' item) and the number of intervening items occurring within this temporal interval. Time based forgetting in short term memory is well documented both in our own laboratory (McKeown, Holt, Delvenne, Smith & Griffiths, 2014;McKeown & Mercer, 2012;Mercer & McKeown, 2014) and elsewhere (Zhang & Luck, 2009), yet the underlying mechanisms of such decline in memory over time are fiercely debated (Altmann & Schunn, 2012;Waugh & Norman, 1965).…”
Section: Time Manages Interference 3 Time Manages Interference In Vismentioning
confidence: 99%
See 2 more Smart Citations
“…The bias towards pattern completion (i.e., incorrectly recognized a "similar" item as an "old" studied item) measured in PweMS appeared to be the counterpart of pattern separation impairment because these two processes work concurrently (Ally et al, 2013). Indeed, previous rodents and human studies have suggested that when dentate gyrus is unable to perform pattern separation, CA3 (and its connections to CA1) could balance this deficit by overwriting previous representations (Neunuebel & Knierim, 2014;.…”
Section: Discussionmentioning
confidence: 92%